Replacement of the Gamma by the Delta variant in Brazil: Impact of lineage displacement on the ongoing pandemic - Giovanetti, Marta; Fonseca, Vagner; Wilkinson, Eduan; Tegally, Houriiyah; San, Emmanuel James; Althaus, Christian L.; Xavier, Joilson; Slavov, Svetoslav Nanev; Viala, Vincent Louis; Jeronimo Lima, Alex Ranieri; Ribeiro, Gabriela; Souza-Neto, Jayme A. [UNESP]; et al. (Oxford Univ Press, 2022)
The coronavirus disease 2019 (COVID-19) epidemic in Brazil was driven mainly by the spread of Gamma (P.1), a locally emerged variant of concern (VOC) that was first detected in early January 2021. This variant was estimated to be responsible for more than 96 per cent of cases reported between January and June 2021, being associated with increased transmissibility and disease severity, a reduction in neutralization antibodies and effectiveness of treatments or vaccines, and diagnostic detection failure. Here we show that, following several importations predominantly from the USA, the Delta variant rapidly replaced Gamma after July 2021. However, in contrast to what was seen in other countries, the rapid spread of Delta did not lead to a large increase in the number of cases and deaths reported in Brazil. We suggest that this was likely due to the relatively successful early vaccination campaign coupled with natural immunity acquired following prior infection with Gamma. Our data reinforce reports of the increased transmissibility of the Delta variant and, considering the increasing concern due to the recently identified Omicron variant, argues for the necessity to strengthen genomic monitoring on a national level to quickly detect the emergence and spread of other VOCs that might threaten global health.
Keywords: Genomic monitoring; variants replacment; Brazil; Gamma; Delta